1984
DOI: 10.1007/bf00328198
|View full text |Cite
|
Sign up to set email alerts
|

Bicaudate diameter?the most specific and simple CT parameter in the diagnosis of Huntington's disease

Abstract: In addition to the neurological findings, the functional capacity of 12 patients with Huntington's disease was evaluated quantitatively according to the Shoulson and Fahn scale [1]. This parameter was related to the following computed tomographic measurements: the greatest distance between the frontal horns (FH), the shortest distance between the heads of the caudate nuclei (bicaudate diameter, CC) and the quotient FH/CC. The ratio of the bicaudate diameter and the external diameter of the skull across the nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
5

Year Published

1986
1986
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 10 publications
2
16
0
5
Order By: Relevance
“…Cutoff values to segregate persons into normal or abnormal categories were calculated. These values were defined as the mean plus or minus two standard deviations, based on previously reported results in normal controls [5,18,23,241. For FWCC a value less than or equal to 2, and for CCiOTcc a value greater than or equal to 0.1 were considered abnormal.…”
Section: Ct Measzlrementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cutoff values to segregate persons into normal or abnormal categories were calculated. These values were defined as the mean plus or minus two standard deviations, based on previously reported results in normal controls [5,18,23,241. For FWCC a value less than or equal to 2, and for CCiOTcc a value greater than or equal to 0.1 were considered abnormal.…”
Section: Ct Measzlrementsmentioning
confidence: 99%
“…who had rated every participant were used for consistency. Combined scores were defined as follows: ported measures of caudate atrophy have correlated however, they have not been associated with the severity of specific neurological findings such as chorea or dystonia in affected individuals [15][16][17][18] Follow-up neurological examinations performed 2 to 6 years after the above examination, and without CT or PET data, were available in 39 of the 54 participants. From these follow-up visits, at-risk individuals who had developed definite chorea were identified and classified as subsequent phenotypical converters.…”
Section: Neu Rological Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, systemically 3-NP-treated animals exhibited significant hyperactivity during the first 2 injections, reaching a plateau after the third injection, and then displaying hypoactivity after the fourth injection [52] . The study by Mettler indicates that small lesions are visible at the onset of hypoactivity, but at the end of the long-term course of 3-NP administration, larger lesions were noted; there is no visible striatal degeneration at the period of hyperactivity [53][54][55] . Despite chronic 3-NP rat models replicating some of the features of HD, this model still has some limitations.…”
Section: In Vivo and In Vitro Models Of Hdmentioning
confidence: 99%
“…It has already been shown that computed tomography (CT) and magnetic resonance imaging (MRI) can be used to measure brain atrophy that is an important anatomical change in the course of several diseases [1][2][3][4] , as well as in normal aging [5][6][7] . Simple linear measurements taken on axial CT slices were used from the advent of imaging technologies; however, different authors have used different exclusion criteria for sample material and for image analysis as well 8 .…”
Section: Introductionmentioning
confidence: 99%